2007
DOI: 10.1007/s10666-006-9063-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of long-term flowering patterns of Box–Ironbark species in Havelock and Rushworth forests

Abstract: Long-term records were used to compare the flowering of Eucalyptus microcarpa, E. melliodora, E. leucoxylon, E. polyanthemos and E. tricarpa between Havelock Forest (1940-1971) and Rushworth District (1945-1970. Indices were developed and used to compare the mean monthly annual flowering patterns (e.g., mean duration, annual flowering success) between the two locations. Additionally, the long-term flowering pattern of each species between 1945 and 1970 was examined for concordance. Results of the analysis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 44 publications
3
44
1
Order By: Relevance
“…budding, seeding) in Eucalypts (Ashton 1975, Bassett 1995, Murray and Lutze 2004. This phenomenon has also been reported specifically in E. tricarpa (Keatley and Murray 2006). The second sub-component, d2, reflects both the duration and the pattern of the original flowering record, for a given species; as shown also earlier for 4 of the 8 species studied in this chapter by Hudson et al (2010a,b).…”
Section: Subcomponentssupporting
confidence: 81%
“…budding, seeding) in Eucalypts (Ashton 1975, Bassett 1995, Murray and Lutze 2004. This phenomenon has also been reported specifically in E. tricarpa (Keatley and Murray 2006). The second sub-component, d2, reflects both the duration and the pattern of the original flowering record, for a given species; as shown also earlier for 4 of the 8 species studied in this chapter by Hudson et al (2010a,b).…”
Section: Subcomponentssupporting
confidence: 81%
“…An intensity value of 0-5 was determined for each provenance derived as a function of the quantity of flowers and the proportion of trees in flower from that provenance (modified from Keatley et al (2004) and Keatley and Hudson (2007)). The quantity score ranged from 0 to 3 and was assigned as follows: 0 = no flowering; 0.5 = <100 flowers; 1 = 101-1000 flowers; 2 = 1001-5000 flowers and 3 = >5000 flowers.…”
Section: Statistical Analysis Flowering Intensity and Synchronymentioning
confidence: 99%
“…We report intensity scores on a monthly basis as appropriate for our analysis but they are usually given as an annual average in long-term flowering studies (e.g. Keatley et al 2004;Keatley and Hudson 2007). An intensity score of zero indicated that no tree from the provenance flowered, whereas a score of five indicated flowering was heavy in that month.…”
Section: Statistical Analysis Flowering Intensity and Synchronymentioning
confidence: 99%
See 2 more Smart Citations